The importance of progesteron for the safety of pregnancy at early and late terms - С. О. Шурпяк; В. І. Пирогова (Publishing House TRILIST, 2019)
Progesterone is a key hormone to support pregnancy and pregnancy onset. Problem of low fertility, infertility is becoming increasingly important, which in turn further exacerbates miscarriage. The aim of this systematic review is to elucidate new information based on current scientific evidence, evidence-based medicine and world clinical protocols, summarize actual knowledge of the importance of sequential use of one type of gestagen for pre-conceptual preparation, treatment, and prevention of the risk of pregnancy termination in different clinical settings. Analysed data indicate that it is natural micronized progesterone to be the drug of choice in the treatment of habitual miscarriage associated with luteal phase deficiency, and it is important to use one type of gestagen at the pre-conception stage. Currently, vaginal drugs of micronized progesterone used to support the luteal phase during IVF cycles due to the relative ease of use and efficiency equivalence to intramuscular progesterone. Vaginal progesterone has advantages due to the effect of primary passage through the uterus, it concentration in endometrial tissues is usually much higher than in serum. An independent, randomized, double-blind, placebo-controlled trial PRISM showed the efficacy of vaginal micronized progesterone in women with genital bleeding early in pregnancy (clinic of abortion). In group of micronized progesterone the rate of live birth was higher by 3% compared to placebo, which in absolute numbers was greater for 54 live births. The best results were achieved in patients with a history of 3 or more miscarriages, where the odds of live birth due to micronized progesterone (Utrogestan®) increased by 28%. Also it is important that Utrogestan® at a dose of 800 mg/day for up to 16 weeks of gestation is safe for the fetus (the frequency of congenital abnormalities did not differ in the vaginal progesterone and placebo group) and did not prevent the rejection of the genetically defective embryo.